Analyzing historic human-suid relationships through dental microwear texture and geometric morphometric analyses of archaeological suid teeth in the Ryukyu Islands. (August 2021) - Yamada, Eisuke; Hongo, Hitomi; Endo, Hideki
Abstract: We investigated human-suid interactions to understand how suids could coexist with humans in the Ryukyu Islands, Japan, for centuries despite the limited carrying capacity of each island and their overlapping nutritional needs with humans. We carried out dental microwear texture analysis (DMTA) and geometric morphometric (GMM) analysis on suid remains excavated from different localities on the Ryukyu Islands to determine their feeding patterns. The DMTA results suggested that humans approximately 7000 to 4400 BP probably reared/kept some suids before slaughter. Their "wild" molar shape suggested that they lived in proximity to the wild ecosystem and were probably not part of the domestic stock. Our results showed that suids belonged to a reared population that was captured by hunting for delayed consumption. The emerging picture is that suids were fed leftovers or other by-products of human activities. Thus, we conclude that suids and humans created an interdependent relationship instead of becoming competitors, which enabled them to coexist on the islands. The DMTA results suggested that the pig husbandry system of the islands varied during the 17th–19th centuries. In the central region of the islands, pigs were fed a much softer diet than natural resources in a floored stall, whereas in the southern region, pigs were allowed to range freely around human settlements. The GMM analysis of the outline shape of the teeth of suids from this period showed that they were morphologically similar to the modern native domestic breed found on the Ryukyu Islands, regardless of geographical setting of each archaeological site. These results suggest that some suids were transported overseas. Highlights: Examination of dental remains reveals suid feeding patterns on Ryukyu Islands. Suid/human commensalism probably enabled coexistence on the Ryukyu Islands. In the Shellmidden period, humans probably reared/kept some suids before slaughter. In the Ryukyu Dynasty periods, some domestic suids were probably transported overseas.